The Application of Health Protocols in the New Normal Era in Aqua Version Advertising with Aqua Goodness, We Continue to Move (Charles Sanders Peirce Model Semiotic Analysis): Penerapan Protokol Kesehatan di Era New Normal Dalam Iklan Aqua Versi Bersama Kebaikan Aqua, Kita Terus Melangkah [Analisis Semiotika Model Charles Sanders Pierce] - Ramdhani, Al Wildan; Aesthetika, Nur Maghfirah (Indonesian Journal of Innovation Studies, 2023)
This study aims to analyze the meaning of the message in advertising Aqua version with the goodness of Aqua, we continue to step. This study uses descriptive qualitative research using Charles Sanders Pierce's semiotic analysis model which will be useful in explaining icons, indexes, and symbols to find the application of health protocols in the new Normal Era in advertisements spread in the mass media. The results of this study state the implementation of health protocols marked in a scene, property, and certain color characteristics that occurred at the interval of the covid-19 pandemic. The findings refer to an appeal that has been submitted by the covid-19 handling task force in the form of rules that must be applied when outside the home in the form of 3M (washing hands, using masks and maintaining distance).